2014
DOI: 10.4209/aaqr.2014.04.0077
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Composition of Ambient Fine Particles in Urban Schools: Sources of Children’s Exposure

Abstract: Currently, there is a limited understanding of the sources of ambient fine particles that contribute to the exposure of children at urban schools. Since the size and chemical composition of airborne particle are key parameters for determining the source as well as toxicity, PM 1 particles (mass concentration of particles with an aerodynamic diameter less than 1 µm) were collected at 24 urban schools in Brisbane, Australia and their elemental compositions determined. Based on the elemental compositions four mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Data summarized in Figure 5 show the comparison of trace metal concentrations in 1996 and in recent years (from 2010 to 2017) in four cities, including Zn, Mn, Pb, Cu, Cr, that are either specific source indicators or trace elements with serious impact on human health (106)(107)(108)(109).…”
Section: Trace Metal Elementsmentioning
confidence: 99%
“…Data summarized in Figure 5 show the comparison of trace metal concentrations in 1996 and in recent years (from 2010 to 2017) in four cities, including Zn, Mn, Pb, Cu, Cr, that are either specific source indicators or trace elements with serious impact on human health (106)(107)(108)(109).…”
Section: Trace Metal Elementsmentioning
confidence: 99%
“…Since PM 2.5 in ambient air is a broadly recognized environmental and public health issue, it has received considerable attention worldwide and is currently regulated in most industrialized countries (WHO 2005). Numerous studies on PM 2.5 and its toxic element constituents were conducted in many countries (Toledoet al 2008;Crilley et al 2014;Morishita et al 2011;Cristaldi et al 2013). China is the world's largest emitter of atmospheric PM 2.5 , and the government has been increasingly taking actions to reduce emissions (Li et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies in the literature (Yamazaki et al, 2015;Yu et al, 2013;Hosseinibalam and Hejazi, 2012;Xiao et al, 2013, Sarasamma andNarayana, 2014;Wang et al, 2012;Manousakas et al, 2013;Crilley et al, 2014; Abu-Allaban and Abu-Qudais, 2011) reported weather conditions from India, USA, Iran, Japan, Kenya, Australia, Greece, Saudi Arabia and Jordan. Reports from this part of the world are scarce and this informed the reason for embarking on this research.…”
Section: Introductionmentioning
confidence: 99%